Fragments of fullerenes and carbon nanotubes : designed synthesis, unusual reactions, and coordination chemistry - Scott, Lawrence T.; Petrukhina, Marina A. (Hoboken, NJ : John Wiley & Sons, 2012)
This book is the first of its kind to reflect upon the intense and rapidly growing interest in open geodesic polyaromatic molecules, specifically focusing on their synthesis and reactivity in metal binding reactions. The book broadly covers all aspects related to the fullerene fragment chemistry: current synthetic techniques, description of the available members of this new family (which has grown to more than two dozens members, with none being available commercially), molecular geometry and trends in the solid state packing, as well as extensions into physical properties and new buckybowl-based molecules and materials. It covers fundamental research related to a new class of hydrocarbons, namely open geodesic polyarenes that map onto the surfaces of fullerenes (and referred to as fullerene fragments or buckybowls.
Molecular Clips and Tweezers with Corannulene Pincers / Andrzej Sygula, Willard E Collier -- Synthesis of Bowl-Shaped and Basket-Shaped Fullerene Fragments Via Benzannulated Enyne-Allenes / Kung K Wang, Hu Cui, Bo Wen -- Anions of Buckybowls / David Eisenberg, Roy Shenhar, Mordecai Rabinovitz -- Curved p-Conjugated Stable Open-Shell Systems Possessing Three-Dimensional Molecular/Electronic Spin Structures / Yasushi Morita, Akira Ueda -- Experimental and Calculated Properties of Fullerene and Nanotube Fragments / Derek R Jones, Praveen Bachawala, James Mack -- Coordination Preferences of Bowl-Shaped Polyaromatic Hydrocarbons / Alexander S Filatov, Marina A Petrukhina -- Sumanenes: Synthesis and Complexation / Toshikazu Hirao, Toru Amaya -- s-Bonded Transition Metal Complexes of Polycyclic Aromatic Carbon Compounds / Paul R Sharp -- Hemispherical Geodesic Polyarenes: Attractive Templates for the Chemical Synthesis of Uniform-Diameter Armchair Nanotubes / Anthony P Belanger, Katharine A Mirica, James Mack, Lawrence T Scott -- Aromatic Belts as Sections of Nanotubes / Gaston R Schaller, Rainer Herges -- Cycloparaphenylenes: The Shortest Possible Segments of Armchair Carbon Nanotubes / Xia Tian, Ramesh Jasti -- Conjugated Molecular Belts Based on 3D Benzannulene Systems / Masahiko Iyoda, Yoshiyuki Kuwatani, Tohru Nishinaga, Masayoshi Takase, Tomohiko Nishiuchi -- Toward Fully Unsaturated Double-Stranded Cycles / Malte Standera, Dieter Schluter -- Bent Pyrenes: Springboards to Aromatic Belts? / Graham J Bodwell, Gandikota Venkataramana, Unikela Kiran Sagar.
Includes bibliographical references and index.
Print version record.
Keywords: Fullerenes; Fragmentation reactions; SCIENCE -- Chemistry -- Inorganic; Fragmentation reactions; Fullerenes; Electronic books; Electronic books